Pengaruh Kompensasi Terhadap Kinerja Karyawan Pada CV Rezky Bahari Makassar - Sulaeman B; Seniorita Seniorita; Ratnawati Ratnawati (Master Manajemen, 2024)
The operations of a company or organization depend heavily on human resources (HR) as the most important component. One factor that significantly influences employee performance improvement is the compensation policy implemented by the company. This research aims to determine the effect of compensation on employee performance at CV Rezky Bahari, a decorative coral supplier company. The research method uses a quantitative approach with data collection techniques through questionnaires whose validity and reliability have been tested. The sample in this study consisted of 22 respondents. The data analysis techniques used are simple linear regression analysis, classical assumption testing, and hypothesis testing. The results of the research show that the constant value of employee performance is 10.899, while the regression coefficient value is 0.538, which means that every time there is an increase in the improvement variable by 1 unit, there will be an increase in employee performance of 0.538 units assuming the other variables are constant. Based on the t test, it can be concluded that partially there is a positive influence between compensation and employee performance. Based on the results of the coefficient of determination test, it can be seen that the R2 value is 0.371. This means that 37% of the variation in employee performance scores can be explained by fulfillment, and the remaining 63% is influenced by other variables.